Market failures and regulatory failures: Lessons from past and present financial crises - Viral V. Acharya; Thomas Cooley; Matthew Richardson; Ingo Walter (Asian Development Bank Institute (ADBI), 2011)
The paper analyzes the financial crisis of through the lens of market failures and regulatory failures. We present a case that there were four primary failures contributing to the crisis: excessive risk-taking in the financial sector due to mispriced government guarantees; regulatory focus on individual institution risk rather than systemic risk; opacity of positions in financial derivatives that produced externalities from individual firm failures; and runs on the unregulated banking sector that eventually threatened to bring down the entire financial sector. In emphasizing the role of regulatory failures, we provide a description of regulatory evolution in response to the panic of 1907 and the Great Depression, why the regulation put in place then was successful in addressing market failures, but how, over time, especially around the resolutions of Continental Illinois, Savings and Loans crisis and Long-Term Capital Management, expectations of too-big-to-fail status got anchored. We propose specific reforms to address the four market and regulatory failures we identify, and we conclude with some lessons for emerging markets.
Keywords: E44; G01; G15; G18; G21; G24; 330; Finanzmarktkrise; Marktversagen; Kapitalmarktliberalisierung; Staatsversagen; Wirtschaftsgeschichte; Welt